Epidemiological and Clinical Parameters Features of Patients with Clonorchiasis in the Geum River Basin, Republic of Korea - Shin, Hee-Eun; Lee, Myoung-Ro; Ju, Jung-Won; Jeong, Byong-Suk; Park, Mi-Yeoun; Lee, Keoung-Sook; Cho, Shin-Hyeong (Interdisciplinary Perspectives on Infectious Diseases, 2017)
This study was conducted to evaluate the infection rates of Clonorchis sinensis and laboratory findings in infected people. The 3,167 fecal samples, from nine villages in Okcheon-gun, were examined.